Josephine March’s Conflicts and Personalities Analysis in the Movie “Little Women (2019)” - Nada Sa’addiyah; Binti Qani’ah (International Journal of Sustainable Applied Sciences, 2024)
In this article, the focus was on the analysis of the conflict and personality of Josephine March the main character in the movie "Little Women (2019)" by Greta Gerwig. This research data was in the form of scenes supported by the movie script. These data were determined based on the type of conflict according to Kenney's theory (1966), then the personality type faced by the main character was analyzed based on Freud's theory (1923). The results show that there were 98 conflict data. The actions of Josephine March in both internal and external conflict demonstrated the presence of the id, ego, and superego personality types. The Id represented her fundamental desires and urges, whereas the ego served to balance these desires within the bounds of reality. The superego was a representation of the social norms and ideals that shape her conduct. She also exhibited a blend of id-ego and ego-superego behaviors, highlighting the complexity of her character as she balanced her innate impulses with the needs of reality and external expectations.